2011
DOI: 10.4049/jimmunol.1003706
|View full text |Cite
|
Sign up to set email alerts
|

Pre-B Cell Colony-Enhancing Factor (PBEF/Nampt/Visfatin) Primes Neutrophils for Augmented Respiratory Burst Activity through Partial Assembly of the NADPH Oxidase

Abstract: Pre-B cell colony-enhancing factor ([PBEF] also known as Nampt/visfatin) is a pleiotropic 52-kDa cytokine-like molecule whose activity has been implicated in multiple inflammatory disease states. PBEF promotes polymorphonuclear neutrophil (PMN) proinflammatory function by inhibiting constitutive PMN apoptosis. We investigated whether PBEF activates or primes for PMN respiratory burst. We found that although PBEF did not activate respiratory burst on its own, it primed for increased reactive oxygen species gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Li et al36 also reported that extracellular PBEF protected macrophages from endoplasmic reticulum stress-induced apoptosis by activating an IL6/STAT3 signaling pathway via a non-enzymatic mechanism of NAMPT. Malam et al37 demonstrated that priming for neutrophil respiratory burst by PBEF (NAMPT) occurred independently of its NAD-generating capacity because neither NM nor NAD could recapitulate the effects and, furthermore, that FK866 could not inhibit priming. Based on these observations, we posit that MC4 may have a higher binding affinity to NAMPT than FK866, which leads to a more severe distorted conformation, resulting in structural constraints not favorable to the interaction of NAMPT with its elusive receptor or other key proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al36 also reported that extracellular PBEF protected macrophages from endoplasmic reticulum stress-induced apoptosis by activating an IL6/STAT3 signaling pathway via a non-enzymatic mechanism of NAMPT. Malam et al37 demonstrated that priming for neutrophil respiratory burst by PBEF (NAMPT) occurred independently of its NAD-generating capacity because neither NM nor NAD could recapitulate the effects and, furthermore, that FK866 could not inhibit priming. Based on these observations, we posit that MC4 may have a higher binding affinity to NAMPT than FK866, which leads to a more severe distorted conformation, resulting in structural constraints not favorable to the interaction of NAMPT with its elusive receptor or other key proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study has shown that NAMPT primes neutrophils for augmented respiratory burst through the generation of reactive oxygen species via NADPH oxidase [80].…”
Section: Nampt Expression In Inflammatory Cellsmentioning
confidence: 99%
“…A potential interaction between PBEF and insulin signaling was first reported by Fukuhara et al (15), although this report was subsequently retracted (16). Others have shown that PBEF can induce the activation of IR␤ (31), Akt (54), ERK, and p38 (41), although the capacity of PBEF to activate IR␤ (54) and Akt (75) has been challenged. Using A549 lung epithelial cells, we found that PBEF itself could not induce the phosphorylation of IR␤ nor activate Akt.…”
mentioning
confidence: 94%
“…First, as a Nampt, PBEF catalyzes the rate-limiting step in a salvage pathway of nicotinamide adenine dinucleotide (NAD) biosynthesis (55). Second, it has proinflammatory activity as an extracellular cytokine-like molecule that is involved in acute and chronic inflammation (38,45), inhibits neutrophil apoptosis (29), and primes neutrophil respiratory burst (41). The third and most controversial function of PBEF is as an alternate ligand for the IR (15).…”
mentioning
confidence: 99%